The Bioinformatics Application in Detecting Germline and Somatic Variants towards Breast Cancer using Next Generation Sequencing - Retnomawarti, Rizka; Panigoro, Sonar Soni; Paramita, Rafika Indah (PT Mattawang Mediatama Solution, 2023)
Breast cancer is the type of cancer with the most and the highest cases causing mortality in Indonesia, so an effective treatment is required to reduce the incidence and mortality rate due to cancer breasts. Most breast cancer patients are diagnosed at an advanced stage so the treatment used are limited and the risk of death becomes higher. Along with the development of human genome sequencing technology, the genetic examination of breast cancer is considered as an examination that can be used for early prevention and treatment management personally. Based on the target variants detected, the genetic examination of breast cancer can be divided into two, namely the examination of germline variants and somatic variants. Germline variant examination is intended to predict the risk of breast cancer which can be used as an early preventive measure, while somatic variant examination is intended for cancer diagnosis and management therapy. NGS technology is able to detect both types of variants in a number of genes associated with breast cancer in several samples effectively and quickly. However, the data generated from NGS technology is very large and complex, so the role of bioinformatics is required in analyzing and interpreting data. By utilizing bioinformatics pipelines and tools, analysis of germline variants and somatic variants in breast cancer can be carried out accurately so that the results of genetic examinations can be used as a step to treat breast cancer.